2020
DOI: 10.1002/jaba.693
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing in‐vivo feedback for caregiver training of pediatric feeding protocols

Abstract: Researchers have used multicomponent behavioral skills training packages including written and verbal instructions, modeling, rehearsal, and feedback when teaching caregivers to implement pediatric feeding treatment protocols (e.g., Anderson & McMillan, 2001; Seiverling et al., 2012). Some investigators have shown that fewer behavioral skills training components may be necessary for effective training (e.g., Mueller et al., 2003; Pangborn et al., 2013). We examined the use of in‐vivo feedback following wri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Although the purpose of the current study was not to evaluate caregiver training procedures, an interesting finding is that caregivers did not require all behavioral skills training components to implement the procedures successfully. Similar to findings of previous studies (e.g., Bachmeyer-Lee et al, 2020), caregivers performed each of the protocol steps correctly with fewer components.…”
Section: Discussionsupporting
confidence: 88%
“…Although the purpose of the current study was not to evaluate caregiver training procedures, an interesting finding is that caregivers did not require all behavioral skills training components to implement the procedures successfully. Similar to findings of previous studies (e.g., Bachmeyer-Lee et al, 2020), caregivers performed each of the protocol steps correctly with fewer components.…”
Section: Discussionsupporting
confidence: 88%
“…Typically, this model is used to teach caregivers to implement treatment at a local site or in the child's natural environment using behavioral skills training (BST; i.e., instruction, model, rehearsal, feedback; Parsons et al, 2012). Variations of BST have been used to teach parents how to implement feeding treatment protocols in the clinic (e.g., Bachmeyer‐Lee et al, 2020; Mueller et al, 2003; Seiverling et al, 2012) and home settings with practitioners providing on‐site training (e.g., Gentry & Luiselli, 2008; Najdowski et al, 2010). Studies have shown the positive outcome of telehealth as it relates to decreasing problem behavior (e.g., Wacker et al, 2013), early intervention for children diagnosed with autism spectrum disorder (ASD; Awasthi et al, 2021), school consultation (e.g., Frieder et al, 2009), and feeding difficulties with children (e.g., Andersen et al, 2021; Bloomfield et al, 2019).…”
mentioning
confidence: 99%
“…Yet, BPT programs that also include in vivo practice with children present in the therapy session show larger effects than programs that do not (Kaminski et al, 2008). In vivo coaching improves parenting skills, even when parents do not receive an in-depth description of or rationale for the skills being taught (Shanley & Niec, 2010) and in vivo feedback increases skills beyond written instruction (Bachmeyer-Lee et al, 2020).…”
mentioning
confidence: 99%